Lactiplantibacillus plantarum NKK20 Alleviates High-Fat-Diet-Induced Nonalcoholic Fatty Liver Disease in Mice through Regulating Bile Acid Anabolism - Chang Sun; Chenguang Qiu; Yanyan Zhang; Man Yan; Jiajun Tan; Jiayuan He; Dakai Yang; Dongxu Wang; Liang Wu (Molecules, 2023)
Nonalcoholic fatty liver disease (NAFLD) is the most prevalent chronic disease in modern society. It is characterized by an accumulation of lipids in the liver and an excessive inflammatory response. Clinical trials have provided evidence that probiotics may prevent the onset and relapse of NAFLD. The aim of this study was to explore the effect of Lactiplantibacillus plantarum NKK20 strain (NKK20) on high-fat-diet-induced NAFLD in an ICR murine model and propose the underlying mechanism whereby NKK20 protects against NAFLD. The results showed that the administration of NKK20 ameliorated hepatocyte fatty degeneration, reduced total cholesterol and triglyceride concentrations, and alleviated inflammatory reactions in NAFLD mice. In addition, the 16S rRNA sequencing results indicated that NKK20 could decrease the abundance of Pseudomonas and Turicibacter and increase the abundance of Akkermansia in NAFLD mice. LC-MS/MS analysis showed that NKK20 could significantly increase the concentration of short-chain fatty acids (SCFAs) in the colon contents of mice. The obtained non-targeted metabolomics results revealed a significant difference between the metabolites in the colon contents of the NKK20 administration group and those in the high-fat diet group, in which a total of 11 different metabolites that were significantly affected by NKK20 were observed, and these metabolites were mainly involved in bile acid anabolism. UPLC-MS technical analysis revealed that NKK20 could change the concentrations of six conjugated and free bile acids in mouse liver. After being treated with NKK20, the concentrations of cholic acid, glycinocholic acid, and glycinodeoxycholic acid in livers of the NAFLD mice were significantly decreased, while the concentration of aminodeoxycholic acid was significantly increased. Thus, our findings indicate that NKK20 can regulate bile acid anabolism and promote the production of SCFA, which can inhibit inflammation and liver damage and thus prevent the development of NAFLD.